IDENTIFYING THE USE OF CANVA APPLICATION IN IMPROVING CREATIVITY IN INTEGRATED SCIENCE COURSES - Rinda Oktaviyani; Putranta, Himawan (PENSA E-JURNAL: PENDIDIKAN SAINS, 2025)
Creativity is an important aspect of the learning process that can improve students' concept understanding and thinking skills. The use of educational technology in the digital era is a potential strategy to support the development of creativity. This study aims to identify the use of the Canva application in improving student creativity in Integrated Science courses. This research uses a descriptive method with a quantitative approach. Data was collected through questionnaires distributed to 35 students selected using a purposive sampling technique. The questionnaire contained 15 statement items related to using the Canva application in the Integrated Science course. The data was analyzed descriptively with the help of Google Forms' data analysis features. The results showed that Canva made it easy for students to create attractive visual content such as infographics, learning media, and project reports. In addition, this application helps students express ideas more creatively and increases their learning motivation. Canva was also shown to improve creativity indicators such as fluency, flexibility, originality, and elaboration, with 54.3% of respondents feeling more creative when using it. The results of this study recommend integrating technology, such as the Canva application, in lecture activities to encourage increased student creativity in understanding Integrated Science materials.